Pelatihan Pembuatan Tempe dan Produk Olahanya serta Pengenalan Kewirausahaan bagi Santriwati Ponpes Tahfidzul Qur'an Ciputat Tangerang - Hugo Aries Suprapto; Mamik Suendarti; Reko Syarif Hidayatullah; Muhammad Sofyan Romdhoni; Ahmad Firdaus Yahya (Jurnal Pengabdian UntukMu NegeRI, 2025)
The activity aimed to enhance teachers' ability at SMA Al-Mubaarok in utilizing AI technology, specifically Chat GPT, as a tool to assist in writing Classroom Action Research (CAR) reports. Through three sessions held in June 2025, teachers received theoretical understanding of CAR, hands-on practice in operating Chat GPT for report writing, as well as continuous evaluation and mentoring. The activity, attended by 15 teachers, was conducted at SMA Al-Mubaarok in Bekasi and employed participatory, demonstrative, needs-based, and sustainable approaches. Evaluation results showed that the average ability of participants reached 81%, with most teachers capable of effectively operating Chat GPT, generating quality draft reports, and quickly obtaining relevant ideas and references. This success indicates that a structured and ongoing training program can accelerate teachers’ adaptation to technological innovations while fostering creativity and professionalism. The use of Chat GPT proved to reduce administrative burden and expedite the report preparation process, supporting improvements in learning quality and teacher professional development. The implications of this activity highlight the importance of continuous socialization and training of technology in the educational environment, as well as fostering a culture of research and innovation among teachers.